2020
DOI: 10.1049/iet-smt.2020.0048
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic technique for analysing the internal faults within power transformers based on sweep frequency response using adjusted R-square methodology

Abstract: The sweep frequency response analysis (SFRA) technique is based on measuring the power transformer electrical transfer functions over a wide frequency range to identify the abnormal areas prior to serious failure. This study presents the proposed diagnostic adjusted R-square technique to identify the transformer faults using the SFRA technique. The SFRA measurements are ranged up to and beyond 1 MHz. The proposed technique is used to calculate the relative factor for adjusted R-square coefficient between the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…At the same time, other factors cause the remaining 1.13%. The R square value of 0.75, 0.50, and 0.25 belongs to the strong, moderate, and weak categories, respectively (Gouda et al, 2020). The results found that non-machine sound is a strong category.…”
Section: Effect Of Non-machine Noise On Hm Bearing Accuracymentioning
confidence: 83%
“…At the same time, other factors cause the remaining 1.13%. The R square value of 0.75, 0.50, and 0.25 belongs to the strong, moderate, and weak categories, respectively (Gouda et al, 2020). The results found that non-machine sound is a strong category.…”
Section: Effect Of Non-machine Noise On Hm Bearing Accuracymentioning
confidence: 83%
“…To evaluate the performances of above-mentioned PGPMs more precisely, Mean Absolute Error, Root of Mean Square Error (RMSE), and Mean Absolute Percentage Error (MAPE) of each PGPM were evaluated and compared. Moreover, a R-square coefficient [26] is also introduced into the paper to calculate the fitting accuracy, which can be expressed by…”
Section: The Quantitative Comparison Of Resultsmentioning
confidence: 99%
“…The coefficient of determination (R 2 ) describes the variation on the dependent variable. R 2 values (Gouda & El-Hoshy, 2020;Jain et al, 2021) indicated the limitations of the dependent variable (Liu & Wang, 2021;Outram et al, 2021). The value ~ one  independent variables provide all information on the dependent variable prediction (Liu & Wang, 2021;Taylor et al, 2021).…”
Section: Resultsmentioning
confidence: 99%